Audiowizualne zawroty głowy. Alfred Hitchcock i wideoeseje - Biliński , Paweł (Załącznik Kulturoznawczy, 2020)
The article focuses on paratexts that refer to the work of Alfred Hitchcock. The author focuses on video essays, which either describe, analyze and interpret films made by the director of Vertigo, or to highlight specific themes that are characteristic of his films. The author briefly examines video essays as a new way of ‘writing’ about the cinema, and draws attention to the popularity of YouTube and Vimeo platforms, commonly used by vloggers to share materials they have edited. The next parts of the article are devoted to video essays thematically focused on Hitchcock and his work. By systematizing the issue and pointing out the most important components of video essays, the author distinguishes the following types of such short films: those that focus on specific themes in Hitchcock’s films; those regarding the director’s method; those examining the influence of his films; those analyzing specific films from different perspectives; those that read Hitchcock’s films in a historical perspective; and finally various video remixes based on the assembly of excerpts of Hitchcock’s works with shots from other films.